ENT 530 Social Media Portfolio : Ollie Hoodies Enterprise / Muhammad Azri Syazwan Mohd Zahari - Mohd Zahari, Muhammad Azri Syazwan (2019)
Ollie Hoodies offers different types of hooded sweatshirt, or commercially mentioned and known as 'hoodie'. Each of the products is distinguished by the main material used in producing the garments, which gives each of them different purposes and characteristics. Our initial concept in launching the product is 'plain and simple'. Thus, most of our products are plain in design, which in our viewpoint, is why it is suitable and wearable in many occasions. As for the price, we provide our customers all type of products at a fixed price of RM32. This is to ensure our potential buyers could afford a high quality garment at a cheaper price than other competitors, as being stated in our m1ss10n. Ollie Hoodies focuses on younger customers, majorly students, since our marketing and operating activities are based in UITM Puncak Alam, Selangor at this earlier stage. Despite not specifying any age of groups for the product, we do consider younger age as our prominent customers, since we believe that they could help our business to achieve its vision.